The Extension of the Victim’s Participation in Non-Prosecution Agreements - Massetto Trevisan, Beatriz (2023)
Brazilian Federal Law #13,964/2019 made several criminal procedural changes. Among them, we find the introduction of the Non-Prosecution Agreement (article 28-A of the Brazilian Criminal Procedure Code). The agreement was conceived as an instrument to ensure the greater efficiency of the Brazilian criminal justice system, aiming to relieve the burden on criminal courts and prosecutors' offices to allow greater attention to the investigation and resolution of cases involving serious and organized crime. Even though the law describes it as a plea deal settled by the defendant and the prosecutor, it also requires compensation for damages caused by the crime, thus giving space to a discussion on the victim's participation in the negotiations. This paper aims to investigate de lege lata, through a literature review methodology, if such participation is possible and, if so, how extensive it should be. For this purpose, we will analyze the aspects extracted from article 28-A and those related to the very raison d’être of the criminal justice system and the modern tendency to revalue the role of the victim.